2019
DOI: 10.17584/rcch.2019v13i1.9720
|View full text |Cite
|
Sign up to set email alerts
|

Planting method, nitrogen fertilization and inoculation for diazotrophic bacteria for Cantaloupe melon plants

Abstract: The objective of this study was to evaluate the effects on plant development, productivity and fruit quality from combinations of planting methods, nitrogen fertilizer applications and inoculation with Azospirillum brasilense in Cantaloupe melons cultivated in a protected environment. A randomized blocks design was adopted with a 2×2×2 factorial scheme with five replications. The treatments consisted of combinations of planting methods (pre-established seedlings or direct field sowing), inoculation with A. bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Unlike what was observed for the other cucurbits, the inoculation of melon plants (Cucumis melo L.) with A. brasilense did not affect the vegetative development of the plants, nor did the relative levels of leaves chlorophyll, a fact related to the initial management of fertilization tanned cattle manure, which enabled better conditions for plant development (Vendruscolo et al, 2019). However, the authors found a positive effect of inoculation on fruit size and yield traits in this same study.…”
Section: Flowers and Fruitscontrasting
confidence: 72%
“…Unlike what was observed for the other cucurbits, the inoculation of melon plants (Cucumis melo L.) with A. brasilense did not affect the vegetative development of the plants, nor did the relative levels of leaves chlorophyll, a fact related to the initial management of fertilization tanned cattle manure, which enabled better conditions for plant development (Vendruscolo et al, 2019). However, the authors found a positive effect of inoculation on fruit size and yield traits in this same study.…”
Section: Flowers and Fruitscontrasting
confidence: 72%